Persepsi Dan Sikap Mahasiswa Universitas Negeri Makassar Terhadap Peredaran Narkoba : Tinjauan Atas Gerakan Anti Narkoba Di Kampus - Alisa Anggreni; A. Octamaya Tenri Awaru; A. Tri Arwina Dheafati (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study was to find out: 1) How are students' perceptions of drug trafficking on campus; 2) What form of anti-drug movement has been carried out by students; 3) How is the anti-drug movement on the Makassar State University campus. This type of research is descriptive qualitative. The technique in determining informants was purposive sampling with the criteria being students of the Faculty of Social Sciences. Data collection techniques used are observation and interviews. The data obtained was analyzed by reducing the data, presenting the data, then drawing conclusions. The data validation technique used source triangulation. The results of the study show that: 1) Students' perceptions of drug trafficking are rejecting and not supporting drug trafficking. 2) Forms of anti-drug movement that have been carried out by students, namely; (a) Participating in commemorating drug day, (b) attending seminars/webinar about the dangers of drug use, (c) participating in spreading broadcasts or information about the dangers of anti-drugs through social media. 3) Forms of the anti-narcotics movement on the Makassar State University campus, namely; (a) Establishing a student activity unit concerned with HIV/AID and drugs (UKM MAPHAN), (b) Organizing seminars/webinar on combating drugs, (c) Participate in the involvement of P4GN (Prevention of Eradication of Abuse and Illicit Circulation of Narcotics).